2022
DOI: 10.1155/2022/1949344
|View full text |Cite|
|
Sign up to set email alerts
|

CX3CL1 Derived from Bone Marrow Mesenchymal Stem Cells Inhibits Aβ1-42-Induced SH-SY5Y Cell Pathological Damage through TXNIP/NLRP3 Signaling Pathway

Abstract: Alzheimer’s disease (AD) is the most commonly seen neurodegenerative brain disorder. The paracrine effects of mesenchymal stem cells (MSCs) signify to trigger immunomodulation and neural regeneration. However, the role and mechanism of bone marrow MSC- (BMSC-) derived CX3CL1 in AD remains elusive. In this study, Aβ1-42-intervened SH-SY5Y cells were used for AD cell model construction. pcDNA-ligated CX3CL1 overexpression plasmids were transfected into BMSCs. The levels of soluble and membrane-bound CX3CL1 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…CX3CR1 is a G protein-coupled receptor, and its downstream signalling pathway is the main connection route between neurons and microglia [36,37]. Many molecules acting as CX3CR1 signal downstream transducers upon FKN binding are known [23,32,36,[38][39][40][41][42] (Table 1). Describing the isoforms of FKN and the mechanisms to generate them is of particular interest when considering that differential activity between soluble and membrane-bound proteins has been reported.…”
Section: Cx3cl1mentioning
confidence: 99%
See 1 more Smart Citation
“…CX3CR1 is a G protein-coupled receptor, and its downstream signalling pathway is the main connection route between neurons and microglia [36,37]. Many molecules acting as CX3CR1 signal downstream transducers upon FKN binding are known [23,32,36,[38][39][40][41][42] (Table 1). Describing the isoforms of FKN and the mechanisms to generate them is of particular interest when considering that differential activity between soluble and membrane-bound proteins has been reported.…”
Section: Cx3cl1mentioning
confidence: 99%
“…They found that BMSC-derived CX3CL1 inhibited cell damage induced by Aβ1-42, as defined by axonal length, cell growth and synaptic protein expressions. In addition, the authors described the putative mechanism underlying their results, that is, the TXNIP/NLRP3 pathway [42]. However, the authors pointed out that the experiments were insufficient to explain either the involvement of BMSC-derived CX3CL1 axis in brain inflammation or which CX3CL1 isoform, between the membrane-bound and the soluble ones, was responsible for reducing Aβ1-42-induced injury in SH-SY5Y cells.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%